Implikasi Pengetahuan Kewirausahaan dan Kreativitas Terhadap Intensi Berwirausaha Siswa Kelas XII SMKN 1 Padang Panjang Tahun Ajaran 2019/2020 - Ulfa Triane; Tri Kurniawati (Universitas Negeri Padang, 2019)
The research aims to determine the effect of entrepreneurial knowledge and creativity on entrepreneurial intentions of students at state vocational high school 1 of Padang Panjang in academic year 2019/2020. The population in this research was all students of class XII SMKN 1 of Padang Panjang in academic year 2019/2020. The samples use are 75 with proportional random sampling technique. The data is analyzed by using multiple regression with SPSS version 20 program. This research use asosiatif quantitative analysis. The results show that the entrepreneurial knowledge has positive and significant effect on entrepreneurial intentions (sig 0,001 < 0,05), and creativity also has positif and significant effect on entrepreneurial intention ( sig 0,000 < 0,05). Keyword: entrepreneurial knowledge, creativity, entrepreneurial intention